2003
DOI: 10.1557/proc-807-303
|View full text |Cite
|
Sign up to set email alerts
|

The Immobilization of Cesium and Strontium in Ceramic Materials Derived from Tungstate Sorbents

Abstract: The effective immobilization of Cs + and/or Sr 2+ sorbed on hexagonal tungsten oxide bronze (HTB) adsorbent materials can be achieved by heating in air at temperatures in the range 500 -1000 °C. Crystalline powdered HTB materials formed by heating at 800 °C show leach characteristics comparable to Cs-containing hot-pressed hollandites in the pH range from 0 to 12. If the Cs-loaded HTB sorbents are pressed into pellets prior to calcination, ceramic monoliths can be prepared. Heating to temperatures in excess of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 2 publications
2
21
0
Order By: Relevance
“…This preliminary study was followed by a detailed characterization of the ion exchange properties of the Mo-doped phase [2]. Following on from this we have demonstrated that such compounds can potentially be converted into leach resistant ceramics [3]. In part 1 of this series we provided a comprehensive evaluation of the leach resistance of the bronze materials generated by heat treatment of Cs-, Sr-and lanthanideloaded HTB ion exchange materials and a more complete description of the phase chemistry of the HTB waste form system.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This preliminary study was followed by a detailed characterization of the ion exchange properties of the Mo-doped phase [2]. Following on from this we have demonstrated that such compounds can potentially be converted into leach resistant ceramics [3]. In part 1 of this series we provided a comprehensive evaluation of the leach resistance of the bronze materials generated by heat treatment of Cs-, Sr-and lanthanideloaded HTB ion exchange materials and a more complete description of the phase chemistry of the HTB waste form system.…”
Section: Introductionmentioning
confidence: 94%
“…The lower temperature exotherm probably represents both the removal of physisorbed water on the surfaces of the MoW-HTB particles and within the structural channels, and partial decomposition of the PAN matrix while the higher temperature exotherm is due to complete combustion of the organic component. The final stages of the PAN matrix removal masks an exotherm routinely observed at 500°C which is characteristic of the decomposition of the HTB framework and the crystallization of WO 3 [2,3]. The region between the end of this decomposition and 1200°C shows minimal weight loss from the sample but between 1200 and 1300°C there was mass loss of approximately 5% from the sample.…”
Section: Thermal Transformation Of Cssr-mow-htb-pan Adsorbentmentioning
confidence: 99%
“…A detailed study of the ion-exchange properties of both the undoped (W-HTB) and Mo-doped materials (MoW-HTB) has been reported recently [6] and a preliminary investigation of the immobilization of the sorbed Cs has also been reported [21]. Because the most effective form of the tungstate adsorbent developed to date is that in which some Mo replaces W in the HTB framework [6] we first address the calcination of this phase in air.…”
Section: Cs-saturated Mo-doped Htbmentioning
confidence: 99%
“…Recently we reported that microcrystalline hydrated hexagonal tungsten bronze (HTB) materials could be used for the simultaneous adsorption of Cs + and Sr 2+ from acidic solutions [6,19,20] and also provided preliminary results indicating that calcination of the Cs-and Sr-saturated HTB materials in air to modest temperatures in the range 600-1000°C could yield highly crystalline materials with very low solubility in the pH range from 0 to 12 [21]. In addition it was demonstrated that higher temperatures result in melting which also produces highly durable materials with little or no Cs volatilization.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated for these materials that it is viable to prepare a durable tailored ceramic directly from Cs-and Sr-saturated hexagonal tungsten bronze (HTB) selective adsorbent compounds with general formula A x WO 3 or A x-M y W 1Ày O 3 where A cations can be Cs or Sr while M is an element that can substitute for W in the hexagonal tungsten bronze framework [38][39][40][41]. Given the potential of GCCs however, it is also of interest to explore the possibility of incorporating the saturated tungstate adsorbents into glass-ceramic composites.…”
Section: Introductionmentioning
confidence: 99%